INNOVATIVE MANAGEMENT: TO THE QUESTION OF INCREASING INNOVATIVE SUSTAINABILITY OF PERSONNEL - Anastasia Valerievna Kutuzova (Science and Innovation Center Publishing House, 2020)
The aim of the present research is to find managerial solutions for decreasing the resistance of the railway personnel to innovations. The article investigates the concept of “innovative receptivity”, its role for innovative management of railway industry companies. Innovative receptivity level of locomotive brigades at the Operating Locomotive Depot is proved by E.A. Laricheva’s method. Necessity of developing the system of innovative personnel receptivity management is also substantiated. We have developed a project for increasing workers’ innovation susceptibility to the average level, which implies the presence of specialists capable to carry out innovative activities and research, as well as the ability of the staff to use the scientific advances of other organizations for managing the innovation process. Our project includes: activities to design a program for the relevant competencies of workers increasing; activities to implement a stimulation of the innovative activity system and development of an information program regarding planned innovations. The social and economic effect of the project was evaluated and the probabilities of risks associated with the proposed activities were identified. We also calculated total cost savings due to the relative freeing-up of the locomotive crews’ employees. The proposed system for managing the innovative receptivity of personnel can be used at similar railway companies.